Cell stress response and hypoxia in breast cancer - Milani, M; Milani Manuela (2011)
During severe hypoxia (<0.01% oxygen) the protein folding machinery becomes dysfunctional, resulting in the accumulation of unfolded proteins with consequent endoplasmic reticulum (ER) stress and activation of the unfolded protein response (UPR) and autophagy, a process involved in the physiological turnover of cytoplasmic components. The link between the UPR and autophagy is not clearly defined. The aim of this thesis is to investigate the role of the induction of UPR under severe hypoxia in tumour survival and resistance to therapy. The results of this research suggest that the activating transcription factor 4 (ATF4), a component of the PKR-like ER kinase (PERK) pathway, fundamental in the UPR, is required for the ER-stress induced upregulation of autophagy. Mechanisms other than hypoxia for UPR induction were investigated, using the proteasome inhibitor bortezomib (BZ). BZ treatment increased ATF4 protein levels in MCF7 cells, even transfected with short-interference RNA (siRNA) against the classical UPR activator PERK, suggesting that the proteasomal stabilization is likely the main mechanism for ATF4 protein accumulation. The induction of autophagy by BZ is dependent upon the upregulation of the microtubule-associated protein 1 light chain 3B (LC3B), an autophagy marker, by ATF4 and acts as a survival mechanism. Hypoxia, UPR and autophagy markers (such as Pimonidazole, carbonic anhydrases IX (CAIX), C/EBP homologous protein (CHOP) and LC3B) were evaluated by immunohistochemical approach in spheroids, xenografts models and breast cancer samples. CHOP immunohistochemical staining was performed in breast cancer sections from a series of patients. CHOP was expressed in cells surrounding necrotic areas. No correlation were found with clinical outcome and further studies are needed.